Influence of restoration type on the cytotoxicity of a 35% hydrogen peroxide bleaching gel - Soares, D. G. [UNESP]; Marcomini, N. [UNESP]; Basso, F. G. [UNESP]; Pansani, T. N. [UNESP]; Hebling, J. [UNESP]; De Souza Costa, C. A. [UNESP] (Operative Dentistry, 2016)
Objectives: The tooth/restoration interface may act as a pathway for hydrogen peroxide (H2O2) diffusion into the pulp chamber. Therefore, the influence of resin-modified glass ionomer cement (RMGIC) and resin composite simulated restorations on the cytotoxicity of an in-office bleaching gel was assessed in vitro. Materials and Methods: Cavities in enamel/dentin discs restored with RMGIC Vitremer (3M ESPE) or Single Bond/Filtek Z350 (3M ESPE) resin composite (RC) were subjected or not subjected to hydrolytic degradation (HD). A 35%-H2O2 bleaching gel was applied to simulated restored and nonrestored enamel surfaces, and culture medium in contact with the dentin substrate (extract) was collected and applied to MDPC-23 cells. Nonrestored discs subjected or not subjected to bleaching were used as positive and negative controls, respectively. Cell viability, oxidative stress, interleukin (IL)-1b expression, alkaline phosphatase (ALP) activity, and mineralized nodule deposition were evaluated. The H2O2 in the extracts was quantified. Data were subjected to statistical analysis.